Pengaruh Kepercayaan dan Kualitas Pelayanan Terhadap Loyalitas Pelanggan Belanja Online Bukalapak (Studi Kasus Pada Pelanggan Usia 17-24 Tahun di Kota Tuban) - Nurdiyanta, Mohammad Fadel Diza; Purwanto, Sugeng (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
This study aims to determine the effect of trust and service quality on online shopping customer loyalty. This research was conducted on online shopping customers of Bukalapak with a case study of customers aged 17-24 years in Tuban City. The number of samples taken as many as 100 respondents with purposive sampling method. Data collection was carried out through distributing questionnaires with samples, namely customers who made purchases on the Bukalapak platform at least once in the last 1 year, aged 17 to 24 years in Tuban City. The analytical technique used is the Partial least squares (PLS) application. results Based on the analysis found that: 1) Trust has a significant positive effect on customer loyalty Bukalapak. 2) Service quality has a significant positive effect on customer loyalty to Bukalapak.